2013
DOI: 10.1063/1.4791785
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle strength on the ballistic resistance of shear thickening fluids

Abstract: The response of shear thickening fluids (STFs) under ballistic impact has received considerable attention due to its field-responsive nature. While efforts have primarily focused on traditional ballistic fabrics impregnated with these fluids, the response of pure STFs to penetration has received limited attention. In the present study, the ballistic response of particle-based STFs is investigated and the effects of fluid density and particle strength on ballistic performance are isolated. It is shown that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Unlike silica, the additives do not contribute to the thickening mechanism because they are not constitutive particles for the STFs. According to Petel et al [35], [36], suspensions of ethylene glycol and SiC particles exhibit shear thinning behavior rather than thickening. For this reason, and the findings will be described in further paragraphs, additive particles negatively influence the thickening behavior of STFs.…”
Section: Effects On Viscosity Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike silica, the additives do not contribute to the thickening mechanism because they are not constitutive particles for the STFs. According to Petel et al [35], [36], suspensions of ethylene glycol and SiC particles exhibit shear thinning behavior rather than thickening. For this reason, and the findings will be described in further paragraphs, additive particles negatively influence the thickening behavior of STFs.…”
Section: Effects On Viscosity Profilementioning
confidence: 99%
“…It was noted that MRSTFs have features of both fluids, but they are more like MR fluids. As well as the magnetic particles in STFs, Petel et al [35], [36] investigated the ballistic resistance of bulk STFs, including carbide particles. According to their studies, carbide particles change the thickening behavior of the STFs while improving its ballistic resistance by increasing the density of this suspension and the dynamic material strength of the fluids.…”
mentioning
confidence: 99%
“…Since the response of these particle-based suspensions are strongly dependent on the stress state within the fluid [7], it should be expected that the multi-dimensional stress state of a ballistic impact would not result in the same level of interparticle stress transfer seen in the plate impact experiments [8]. Evidence from ballistic experiments has demonstrated that the particle material choice strongly influences performance [4,5,9]. In fact, the study by Kalman et al has shown that Kevlar fabrics embedded with dry silica particles outperform fabrics embedded with a silicabased STF [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the suggested protective applications for these particle-based STFs, the strength limitations of these fluids at high strain rates have received little attention. In the present study, an estimate of the effective dynamic strength of a silica-based STF is investigated from available ballistic penetration data [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Another unique aspect is the reversibility of this effect as the STFs will return to fluid state once the shear force is removed or reversed, making it advantageous as a reusable product in applications. Current applications with STFs include scenarios which require energy adsorption from sharp projectiles such as knife or spike attacks [1][2][3][4][5][6][7][8][9][10][11], acoustic and mechanical vibrational dampening control [12,13] and in a passive capacity in other polymeric materials [14][15][16]. The theory of shear thickening includes an order-disorder transition of particles [17,18] and formation of clusters, otherwise known as "hydroclusters" [19][20][21][22] that only form once the applied shear forces overcome particle repulsion forces.…”
Section: Introductionmentioning
confidence: 99%